Punks Not Dead! - Clete, Andrew Bonifacio L. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
On the day of module distribution and retrieval, a mother complains to her son’s teacher regarding a discriminating item: “Ang tattoo ay simbolo ng pagiging kriminal.” As she shows her tattoo “Punks Not Dead,”another parent who happens to be a police man drops by. As the characters argue about the item, the play shows what’s permanently inked with prejudice.